Instructional Technology of Its Development toward Prospective Arts Teachers in Junior and Senior High School Level. - Yofita Sandra; Z. Mawardi Effendi; Atmazaki; Darmansyah (Fakultas Ilmu Pendidikan UNP)
The increasing number of students who enroll the Visual Art Department from year to year opens opportunities for increased art activities in Fine Arts. This increasing lead to activity as the core provision for prospective art teachers. Unfortunately, only few students who take advantage of this valuable moment as an effort to explore their future career. This phenomenon is important to be follow up as a consideration, due to opportunities for future students to run the business, becoming an artist, or even a curator. With such open chance career span they may live, basically when they are study in S1 Visual Arts, all of their knowledge and skills must be obtained from lecturers theoretical and practical. Lecturers are required to develop a suitable learning model, approach, instructional media, learning strategies, as well as reliable visual arts learning techniques. This theoretical paper will explore and summary several findings done by the expert and researcher (lecturers) about preparing instructional technology of its development for prospective art teachers in junior high school, high school/vocational school level. Finally, the paper describe how can students and lecturer gain beneficial from art activities carry on each semester.